(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Socio-Economic Characteristics of the Traditional Fishermen Community of Pengambengan Village, Negara District, Jembrana Regency, Bali Province. Pengambengan Village is one of the coastal areas in the Province of Bali. The research objective was to determine the social characteristics and economic characteristics of the fishermen community in Pengambengan Village. The sampling technique used purposive sampling with a total sample of 93 fishermen. Data collection in this study used a survey method using structured questionnaires and was carried out from the end of May to the end of June 2022. The results showed that traditional fishing communities have social characteristics, including collaborating with fishermen in providing initial capital for going to sea, having close communication with fellow fishermen, and even though the social status of traditional fishermen is different, they still have the same rights within the fishermen group. The economic characteristics of fishermen seen from the income earned are the poor with an average monthly income of Rp1,534,132.62/respondent with an R/C ratio of 1.25, which means that fishing is economically feasible to do even though it is still not profitable. Therefore fishermen need to get assistance to increase knowledge about the use of modern technology in fishing in order to reduce costs and risk of losses experienced.